2003
DOI: 10.1016/s0003-2670(03)00791-8
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical oxidation of l-cysteine mediated by a fullerene-C60-modified carbon electrode

Abstract: Use of a glassy carbon electrode modified by adhered microcrystals of fullerene-C60 mediates the oxidation of cysteine in the presence of aqueous potassium-containing electrolytes. Under conditions of cyclic voltammetry, the potential for the oxidation of cysteine is lowered by approximately 100 mV and current is enhanced significantly relative to the situation prevailing when a bare glassy carbon electrode is used. Additional mediation occurs when the potential range covered includes that of C60/C60n− redox c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
58
0
1

Year Published

2005
2005
2010
2010

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 108 publications
(64 citation statements)
references
References 25 publications
5
58
0
1
Order By: Relevance
“…It well known, the electrochemical behavior of l-cysteine (pKa 1 ¼ 1.92, pKa 2 ¼ 8.37, pKa 3 ¼ 10.70) [7] is dependent on the pH value of the aqueous solution, whereas the electrochemical properties of Fc/Fc þ redox couple are independent pH. Therefore, we studied the electrochemical behavior of l-cysteine in 0.1 M phosphate buffered solution with various pH (2.00 < pH < 9.00) at the surface of FCMCPE by cyclic voltammetry.…”
Section: Electrooxidation Of L-cysteine At the Surface Of Fcmcpementioning
confidence: 99%
See 1 more Smart Citation
“…It well known, the electrochemical behavior of l-cysteine (pKa 1 ¼ 1.92, pKa 2 ¼ 8.37, pKa 3 ¼ 10.70) [7] is dependent on the pH value of the aqueous solution, whereas the electrochemical properties of Fc/Fc þ redox couple are independent pH. Therefore, we studied the electrochemical behavior of l-cysteine in 0.1 M phosphate buffered solution with various pH (2.00 < pH < 9.00) at the surface of FCMCPE by cyclic voltammetry.…”
Section: Electrooxidation Of L-cysteine At the Surface Of Fcmcpementioning
confidence: 99%
“…Therefore, the electrochemical detection of lcysteine has been shown to be facilitated by electrode modification with substituted and unsubstituted transition metal phthalocyanines adsorbed or immobilized onto a graphite electrode [4,5] as well as when a glassy carbon electrode is coated with conductive polymeric films [6]. Such electrode modifications have the objective of increasing the stability of the electrode response, decreasing the overpotential associated with the electrode process, and /or increasing the oxidative current of the sulfuryl compound [7]. These chemically modified electrode electrocatalytic systems also are used to minimize problems with poor selectivity and sensitivity commonly associated with the use of solid electrodes [1].…”
Section: Introductionmentioning
confidence: 99%
“…The modification of electrodes with suitable electron transfer mediators enables the electrochemistry of this compound to proceed at lower overpotential with much higher sensitivity. Also, such electrode modifications have the objective of increasing the stability of the electrode process, and/or increasing the oxidative current of the sulfuryl compound [3]. These chemically modified electrodes as electrocatalytic systems are also used to minimize the problems with poor selectivity and sensitivity that are commonly associated with the use of solid electrodes [4].…”
mentioning
confidence: 99%
“…Previous voltammetric studies of sulphydryl compounds such as glutathione, 2-mercaptoethanol, TA and cysteine have shown that thiol oxidation usually occurs at high electrode potentials in the absence of a catalyst [26][27][28] was analysed in a pH 2 buffer has previously been assigned to such electrodeadsorbed species [26]. In the absence of a catalyst the oxidation of TA requires much higher applied potentials (a large overpotential) than predicted by the zero current measurements, as observed in the DPVs in Fig 3. At pH 2 and 8 the oxidation peak at 1.3 V has previously been assigned to the reaction in Eq.…”
Section: Discussionmentioning
confidence: 64%